Aligned magnetic field on williamson fluid over a stretching sheet with newtonian heating - Hasmawani, Hashim; Norhafizah, Md Sarif; Mohd Zuki, Salleh; Muhammad Khairul Anuar, Mohamed (IOP Publishing, 2020)
Boundary layer flow and heat transfer on Williamson fluid over a stretching sheet is numerically investigated. This paper has been conducted with aim to address how to extend the mathematical formulation for the aligned magnetic field on Williamson fluid over a stretching sheet with Newtonian Heating and how does the effects of several parameters with thermal boundary condition of Newtonian heating in the temperature and velocity profiles. The main objectives of this study are to extend the mathematical formulation and solve numerical algorithms for computations by using Runge-Kutta-Fehlberg (RKF45) technique and analyze the influence aligned angle, magnetic field parameter, Williamson fluid, Prandtl number and conjugate parameter in the term of distribution velocity and temperature are presented graphically. The finding revealed that increasing Williamson fluid parameter, resulted in negative value due to opposite direction between fluid flow and stretching sheet. Increasing on values of Prandtl number results to a decrease in temperature profile. Further, increasing the conjugate parameter resulted to the increased in boundary layer thickness and increasing the magnetic field parameter results to reduced the velocity profile.